First cycle of user experience on assistive courseware for young low vision (AC4LV) learners - Aziz, Nurulnadwan; Abdul Mutalib, Ariffin; Sarif, Siti Mahfuzah (2015)
Reviews from literatures indicate that content application such as courseware which is specifically designed to cater the needs of low vision learners in learning is highly scarce. It was found that most of the existing content applications including courseware focus to the needs of normal student, in which most of this courseware mean too little to the low vision learners in terms of information accessibility, navigation-ability, and pleasure aspects. Having developed the intended courseware which is called as AC4LV it has to be tested to the targeted subjects.Thus, this study presents the first cycle of user experience testing related to the subjects’ behaviors and reactions on AC4LV in effort to make it as one of the effective learning tools specifically for low vision children. It is called as user experience I.In user experience I, 8 subjects with the average age nine to 12 were involved. At this stage, observation was utilized as the data collection method.